1995
DOI: 10.1111/j.1532-5415.1995.tb06385.x
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Model for Predicting Postoperative Delirium in Older Patients Undergoing Elective Orthopedic Surgery

Abstract: A simple model using clock-drawing scores and male gender for preoperative identification of elective patients at greatest risk for POD appears sensitive, predictive, and practical for the preadmission clinic setting, but it should be validated in a prospective trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
1
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 20 publications
6
90
1
1
Order By: Relevance
“…The negative results of Figiel et al, 42 Fisher and Flowerdew, 26 and WilliamsRusso et al 21 could be explained by the healthier and less-demented population they studied. Other probable risk factors include advanced age, abnormal blood urea nitrogen/creatinine ratio, abnormal sodium or potassium level, alcohol abuse, sensory impairment, and medications.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…The negative results of Figiel et al, 42 Fisher and Flowerdew, 26 and WilliamsRusso et al 21 could be explained by the healthier and less-demented population they studied. Other probable risk factors include advanced age, abnormal blood urea nitrogen/creatinine ratio, abnormal sodium or potassium level, alcohol abuse, sensory impairment, and medications.…”
Section: Discussionmentioning
confidence: 66%
“…Schor et al 38 and Bergmann and Eastham, 31 respectively, found living in an institution and having little contract with relatives to be risk factors. Race, 34 marital status, 34 education, 26 and first language other than English 26 had no association.…”
Section: Risk Factor Analysismentioning
confidence: 89%
See 3 more Smart Citations